Visual acuity measurements in a national sample of British elderly people. Issue 2 (1st February 2000) - van der Pols, J C; Bates, C J; McGraw, P V; Thompson, J R; Reacher, M; Prentice, A; Finch, S
Abstract : BACKGROUND: Despite the fact that visual function has an important role in the quality of life in later years, very few studies have measured visual acuity in population based nationwide samples of British elderly people. Such measurements were carried out in the context of the national diet and nutrition survey of people aged 65 years or over (NDNS). METHODS: NDNS participants, who were living in 80 different randomly selected postcode areas of mainland Britain, were visited at their home by a nurse who measured visual acuity at 3 metres, using the Glasgow acuity card (GAC) method. In addition, a brief questionnaire related to ocular health was administered. RESULTS: Visual acuity was measured in 1362 NDNS participants who were not classified as mentally impaired. Visual impairment (using the WHO low vision criteria) was measured in 195 (14.3%) subjects. Prevalence of visual impairment increased significantly with age (65–74 years 3.1%; 75–84 years 11.6%; 85+ years 35.5%, p<0.001 for trend). Impaired vision was more common in subjects living in a nursing home (odds ratio adjusted for age 2.59 (95% CI 2.23 to 2.96)) and in women (odds ratio adjusted for age 1.55 (95% CI 1.21 to 1.89)). 132 (9.7%) subjects had previously undergone cataract surgery and another 157 (11.5%) had been told that they currently had cataract. Vision improved 0.2 log units or more (at least one Snellen line) with the aid of a pinhole occluder in 289 subjects (21.2%). CONCLUSION: Results of this nationwide, community based study confirm that problems with poor distance visual acuity exist in a substantial part of the elderly community, particularly in women and people living in nursing homes.